Unlocking health insights: exploring intention to adopt district health information systems in Bahir Dar City, northwest Ethiopia - Guadie, Habtamu Alganeh; Kindie, Amarech; Derseh, Hunegnaw Almaw; Atnafu, Desta Debalkie (Frontiers in Digital Health, 2025)
BackgroundDistrict Health Information System version 2 (DHIS2) is an open-source platform designed for data collection, processing, analysis, and visualization within healthcare systems. However, there is limited empirical evidence regarding health professionals’ intentions to use district health information systems. Understanding the factors influencing health workers’ intention to utilize DHIS2 is crucial for ensuring successful implementation and sustained usage. This study aimed to assess the intention to use DHIS2 and identify associated factors among health professionals in health centers of Bahir Dar Metropolitan City, Ethiopia, in 2022.MethodsAn institutional-based cross-sectional study was conducted involving 368 randomly selected health professionals from health centers in Bahir Dar City, Ethiopia, between 24 May and 24 June 2022. Data were collected using a structured, self-administered questionnaire. Completed questionnaires were entered and coded in EpiData version 4.6 and exported to SPSS version 25 for cleaning and statistical analysis. Descriptive statistics and bivariate and multivariable logistic regression analyses were performed. Model fitness was assessed using the Hosmer–Lemeshow goodness-of-fit test, with statistical significance set at a p-value < 0.05 and a 95% confidence interval.ResultsA total of 342 participants completed the study, resulting in a response rate of 92.9%. The sample included 176 (51.5%) women, of whom 147 (43%) were nurses. Nearly two-thirds (65.2%) of health professionals expressed an intention to use the DHIS2 system. The intention to use DHIS2 was significantly associated with factors including attitude, computer skills, perceived utility, and perceived ease of use.ConclusionThe findings indicate that attitude, perceived utility, perceived ease of use, and computer skills significantly influence the intention to utilize DHIS2. Therefore, it is imperative to implement targeted interventions before system rollout, including practice-based training, fostering positive attitudes, and enhancing knowledge of the system's usability and functionality to improve the adoption of the district health information system.